Nuclear membrane diversity: underlying tissue-specific pathologies in disease?. (June 2015) - Worman, Howard J; Schirmer, Eric C
Abstract : Human 'laminopathy' diseases result from mutations in genes encoding nuclear lamins or nuclear envelope (NE) transmembrane proteins (NETs). These diseases present a seeming paradox: the mutated proteins are widely expressed yet pathology is limited to specific tissues. New findings suggest tissue-specific pathologies arise because these widely expressed proteins act in various complexes that include tissue-specific components. Diverse mechanisms to achieve NE tissue-specificity include tissue-specific regulation of the expression, mRNA splicing, signaling, NE-localization and interactions of potentially hundreds of tissue-specific NETs. New findings suggest these NETs underlie tissue-specific NE roles in cytoskeletal mechanics, cell-cycle regulation, signaling, gene expression and genome organization. This view of the NE as 'specialized' in each cell type is important to understand the tissue-specific pathology of NE-linked diseases.